2014
DOI: 10.1007/s00468-014-1106-y
|View full text |Cite|
|
Sign up to set email alerts
|

Carbon isotope discrimination, radial growth, and NDVI share spatiotemporal responses to precipitation in Aleppo pine

Abstract: Manuscript Click here to download Manuscript: del Castillo et al manuscript_REV20140828.doc Click here to view linked References 2 Key message. A common pattern in Aleppo pine Δ 13 C responses to both spatial and temporal variability in precipitation was observed, with a general agreement between NDVI, Δ 13 C and growth that confirms precipitation as key environmental driver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 33 publications
(58 reference statements)
3
17
0
Order By: Relevance
“…Consistent with this notion, Leavitt et al (2008) in the southwestern United States found a positive relationship between isotope indices of pinyon pine ( P. edulis and P. monophylla ) and summer NDVI, revealing a potential for long‐term assessment of carbon cycling. Similarly, del Castillo et al (2015) detected a positive association between Δ 13 C and either mean annual NDVI ( r = 0.65) or summer NDVI ( r = 0.69) in Spain, which agrees with our study. This means that high greenness or photosynthetic activity during these months is coupled with lower δ 13 C (more negative), higher discrimination, and lower iWUE, explained by a higher stomatal conductance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with this notion, Leavitt et al (2008) in the southwestern United States found a positive relationship between isotope indices of pinyon pine ( P. edulis and P. monophylla ) and summer NDVI, revealing a potential for long‐term assessment of carbon cycling. Similarly, del Castillo et al (2015) detected a positive association between Δ 13 C and either mean annual NDVI ( r = 0.65) or summer NDVI ( r = 0.69) in Spain, which agrees with our study. This means that high greenness or photosynthetic activity during these months is coupled with lower δ 13 C (more negative), higher discrimination, and lower iWUE, explained by a higher stomatal conductance.…”
Section: Discussionsupporting
confidence: 93%
“…Traditional approaches to assessing forest response to climate do not typically consider how landscape processes interact with CO 2 to control physiological performance at large scales. Indeed, few studies have attempted to link physiological parameters of trees with remotely sensed data of forest productivity, which is a necessary step toward elucidating ecological and biogeochemical changes spatially and over time (del Castillo et al, 2015; Leavitt et al, 2008; Levesque et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both radial growth and D 13 C are influenced by water availability in drought-prone environments, so their association increases in parallel with an enhanced frequency and intensity of drought episodes. Hence, where D 13 C is more responsive to variations in water availability, D 13 C i and TRW i share a robust temporal signal, as shown at the regional level for P. halepensis (del Castillo, Voltas & Ferrio 2015). In this regard, it is expected that pines when more exposed to drought (i.e.…”
Section: R E L a T I O N S H I P S D E P E N D O N T H E A L T I T U mentioning
confidence: 89%
“…) and in the French Alps (Gagen, McCarroll & Edouard ). Conversely, Δ 13 C i was positively related to spring and early autumn precipitation at low and mid‐elevations (del Castillo, Voltas & Ferrio ), suggesting that cambial activity slows down during summer because of water shortage in sub‐Mediterranean pinewoods (Voltas et al . ).…”
Section: Discussionmentioning
confidence: 99%